Analysis of Students' Mathematical Reasoning Skills In Problem-Solving Related to SPLDV Material - Marlinda Indah Eka Budiarti; fitri Cahaya; Muhammad Guvron; Doriana Damaris; Nova Yuliani (Journal of Teaching and Learning Mathematics, 2026)
This study aims to analyze the mathematical reasoning abilities of first-semester Mathematics Education students in solving contextual problems on the topic of Systems of Linear Equations with Two Variables (SPLDV). This study employed a qualitative descriptive method with a sample of 14 students from Muhammadiyah University of Sorong. The research instruments consisted of three story problems based on real-life situations and triangulation interviews to validate the written test results. The analysis of mathematical reasoning ability was conducted based on the indicators of making conjectures, mathematical manipulation, providing evidence, and drawing conclusions. The results of the study indicate that the students’ mathematical reasoning ability achieved an average score of 69.4, with 43% in the high category, 21% in the moderate category, and 36% in the low category. Students in the high category were able to fully and accurately meet all mathematical reasoning indicators. Students in the moderate category were able to meet most of the indicators but still struggled with drawing final conclusions. Meanwhile, students in the low category struggled with transforming problems into mathematical forms, performing mathematical manipulations, and providing appropriate evidence. Based on the research results, it is recommended that instructors provide contextual problem-solving exercises more frequently and encourage students to write down the proof process and final conclusions to improve students’ mathematical reasoning skills.